PEMBERDAYAAN DAN PENGEMBANGAN USAHA MIKRO MENUJU ERA ENDEMI - Novita Wahyu Setyawati; Dewi Sri Woelandari Pantjolo Giningroem; Agus Dharmanto (JURNAL PENGABDIAN MANDIRI, 2022)
Community service activities that will be carried out in the form of community empowerment at the location of service and development of business products and marketing based on digital marketing.The target audience in this Community Service activity are local residents, local officials, existing micro-enterprises, and external parties in terms of marketing. The implementation of community service is carried out by counseling first and then providing assistance to the practice of these activities until finally at the evaluation stage of the activity. Where it is not only limited to practice but assistance in making these products have added value and product marketing based on digital marketing. The benefits obtained from this Community Service activity include being able to create business opportunities, independent villages, developing micro businesses, helping to increase the selling value of products, digital marketing and creating new job opportunities.